New insights at the interface between leprosy and immune-mediated rheumatic diseases - Cruz, Vitor Alves; Albuquerque, Cleandro Pires de; Guimarães, Maria Fernanda Brandão de Resende; Dionello, Carla da Fontoura; Ribeiro, Sandra Lúcia Euzébio; Souza, Viviane Angelina de; Gomes, Ciro Martins; Mota, Licia Maria Henrique da (Frontiers in Medicine, 2023)
Leprosy is an infectious and contagious disease of slow evolution, triggered by Mycobacterium leprae. Arthritis is its third most common manifestation, after cutaneous and peripheral nerve involvement. Since musculoskeletal symptoms may be the initial presentation of the disease, it is important for health professionals to recognize its rheumatic manifestations, for early diagnosis and appropriate treatment, especially in endemic areas. In addition, cases of leprosy have increased globally, notably in patients undergoing treatment with TNF-α blockers and due to the increase in migration and travel of people from developing to developed countries. This review proposes to discuss the main scenarios of mimicry of different rheumatic diseases by leprosy, as well as the role of immunosuppressive drugs used in rheumatology practice in the treatment of reactional states and in the risk of developing the infection.